Rational Design of High‐Concentration Ti3+ in Porous Carbon‐Doped TiO2 Nanosheets for Efficient Photocatalytic Ammonia Synthesis. Issue 9 (29th January 2021) - Han, Qing; Wu, Chongbei; Jiao, Haimiao; Xu, Ruoyu; Wang, Yuze; Xie, Jijia; Guo, Qian; Tang, Junwang
Abstract: Photocatalytic ammonia synthesis is exciting but quite challenging with a very moderate yield at present. One of the greatest challenges is to develop highly active centers in a photocatalyst for N2 reduction under ambient conditions. Herein, porous carbon‐doped anatase TiO x (C‐TiO x ) nanosheets with high‐concentration active sites of Ti 3+ are presented, which are produced by layered Ti3 SiC2 through a reproducible bottom‐up approach. It is shown that the high‐concentration Ti 3+ sites are the major species for the significant increase in N2 photoreduction activity by the C‐TiO x . Such bottom‐up substitutional doping of C into TiO2 is responsible for both visible absorption and generation of Ti 3+ concentration. Together with the porous nanosheets morphology and the loading of a Ru/RuO2 nanosized cocatalyst for enhanced charge separation and transfer, the optimal C‐TiO x with a Ti 3+ /Ti 4+ ratio of 72.1% shows a high NH3 production rate of 109.3 µ mol g −1 h −1 under visible‐light irradiation and a remarkable apparent quantum efficiency of 1.1% at 400 nm, which is the highest compared to all TiO2 ‐based photocatalysts at present. Abstract : A porous carbon‐doped anatase TiO x (C‐TiO x ) nanosheet with controllable Ti 3+ concentration is prepared by a reproducible bottom‐up strategy. The optimal C‐TiO x with high‐concentration Ti 3+ exhibits a NH3 production rate of 109.3 µmol g –1 h –1 under visible‐light irradiation and a remarkable apparent quantum efficiency of 1.1% at 400 nm, the highest compared with all previously reported TiO2 ‐based photocatalysts.